2016
DOI: 10.1016/j.neuroimage.2016.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging measures of error-processing: Extracting reliable signals from event-related potentials and functional magnetic resonance imaging

Abstract: Error-related brain activity has become an increasingly important focus of cognitive neuroscience research utilizing both event-related potentials (ERPs) and functional magnetic resonance imaging (fMRI). Given the significant time and resources required to collect these data, it is important for researchers to plan their experiments such that stable estimates of error-related processes can be achieved efficiently. Reliability of error-related brain measures will vary as a function of the number of error trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 67 publications
6
42
1
1
Order By: Relevance
“…Following interpolation, data were referenced to the average of all electrodes. All participants included in the ERP and current source analyses had a minimum of 10 artifact-free incongruent-error trials ( M = 29.05, SD = 11.52), which has been shown to elicit a reliable measurement of the ERN in both children and adults (Pontifex et al, 2010; Steele et al, 2016). Further, the number of artifact-free error trials did not correlate with age (r = .216, p = .164).…”
Section: Methodsmentioning
confidence: 99%
“…Following interpolation, data were referenced to the average of all electrodes. All participants included in the ERP and current source analyses had a minimum of 10 artifact-free incongruent-error trials ( M = 29.05, SD = 11.52), which has been shown to elicit a reliable measurement of the ERN in both children and adults (Pontifex et al, 2010; Steele et al, 2016). Further, the number of artifact-free error trials did not correlate with age (r = .216, p = .164).…”
Section: Methodsmentioning
confidence: 99%
“…While an important benefit of resampling techniques in general are the improved estimates of population parameters, the primary purpose of implementing these techniques was to remove any bias associated with uneven trail counts by equating the number of trails in each subject‐electrode‐condition average. Indeed, previous research has shown that the number of trails used in each average affects the reliability of the measures extracted from ERPs (J. Cohen & Polich, ; Olvet & Hajcak, ; Pontifex et al, ; Steele et al, ). Thus, in the current study, resampling and bootstrapping methods used in previous research (Watts et al, ) were employed.…”
Section: Methodsmentioning
confidence: 99%
“…Only the feedback phase (combining wins across all types of trials) was analyzed in the present study, because it offers the most power for statistical analysis (i.e. number of trials is not limited by participant selections) (Jones, Cservenka, & Nagel, 2016; Steele et al, 2016). During this phase, the screen indicated whether the participant won or did not win money during that trial, as well as the cumulative dollar amount won up to that point.…”
Section: Methodsmentioning
confidence: 99%